IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) MENGGUNAKAN MEDIA POWERPOINT INTERAKTIF PADA PELAJARAN IPAS DI KELAS V SD NEGERI 1 SUKAWATI GIANYAR TAHUN 2024/2025 - Cahyani, Ni Luh; Selasih, Ni Nengah; Prathiwi, Kd Jayanthi Riva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the strategic role of education in improving the quality of human resources. However, learning practices in elementary schools are still dominated by conventional approaches, resulting in low student engagement, critical thinking skills, and learning outcomes, particularly in the subject of IPAS. The Problem Based Learning (PBL) model is considered an effective alternative as it promotes active and contextual learning through real-life problem solving. The integration of PBL with interactive PowerPoint media is expected to enhance students’ motivation, conceptual understanding, and learning outcomes. This study aims to: (1) analyze the steps of implementing the PBL model using interactive PowerPoint media in IPAS learning for fifth-grade students at SD Negeri 1 Sukawati Gianyar, (2) identify the challenges encountered during its implementation, and (3) determine the impact of the model on students’ learning processes and outcomes. This research employs a qualitative approach, with the principal, fifth-grade teacher, and students as the research subjects. Data were collected through observation and interviews. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Research The results of the study indicate that the implementation of the interactive PowerPoint-based Problem Based Learning (PBL) model was carried out through three stages, namely planning, implementation, and evaluation. The obstacles encountered included time management, classroom dynamics, differences in students’ abilities, teachers’ readiness in lesson planning, and the adaptation process to innovative learning. The implementation of this model had positive impacts in the form of increased learning motivation, student participation and activeness, critical thinking and problem-solving skills, understanding of the material and learning outcomes, effectiveness and conduciveness of the learning process, as well as encouraging changes in teachers’ teaching methods to become more innovative and student-centered.